Age‐related DNA methylation on Y chromosome and their associations with total mortality among Chinese males. Issue 3 (4th February 2022) - Li, Guyanan; Wang, Chenming; Guan, Xin; Bai, Yansen; Feng, Yue; Wei, Wei; Meng, Hua; Fu, Ming; He, Meian; Zhang, Xiaomin; Lu, Yanjun; Lin, Yong; et al.
Abstract: In view of the sex differences in aging‐related diseases, sex chromosomes may play a critical role during aging process. This study aimed to identify age‐related DNA methylation changes on Y chromosome (ChrY). A two‐stage study design was conducted in this study. The discovery stage contained 419 Chinese males, including 205 from the Wuhan‐Zhuhai cohort panel, 107 from the coke oven workers panel, and 107 from the Shiyan panel. The validation stage contained 587 Chinese males from the Dongfeng‐Tongji sub‐cohort. We used the Illumina HumanMethylation BeadChip to determine genome‐wide DNA methylation in peripheral blood of the study participants. The associations between age and methylation levels of ChrY CpGs were investigated by using linear regression models with adjustment for potential confounders. Further, associations of age‐related ChrY CpGs with all‐cause mortality were tested in the validation stage. We identified the significant associations of 41 ChrY CpGs with age at false discovery rate (FDR) <0.05 in the discovery stage, and 18 of them were validated in the validation stage ( p < 0.05). Meta‐analysis of both stages confirmed the robust positive associations of 14 CpGs and negative associations of 4 CpGs with age (FDR<0.05). Among them, cg03441493 and cg17816615 were significantly associated with all‐cause mortality risk [HR(95% CI) = 1.37 (1.04, 1.79) and 0.70 (0.54, 0.93), respectively]. Our results highlighted the importance of ChrY CpGs on male aging. Abstract : The methylation levels of 18 CpGs on Y chromosome in peripheral blood were found to be significantly associated with age. The methylation levels of TTTY14 and EIF1AY were negatively associated with their gene expression levels. The methylation levels of cg03441493 and cg17816615 were significantly associated with all‐cause mortality risk among Chinese males.